Mudharabah Perspektif Al-Syaibani: Aksiologi Ibadah dalam Model Asuransi Syariah - Riska Renvrita Putri; Yoiz Shofwa Shafrani; Samsul Huda (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This research examines Al-Syaibani's perspective on the mudharabah contract as the foundation of a sharia insurance model, with a focus on the axiological values of worship contained within it. Mudharabah is understood not merely as an economic contract but also as a form of worship that upholds principles of justice, shared responsibility, and moral integrity in risk mitigation through a fair profit-sharing system. The mudharabah-based sharia insurance model is seen as capable of becoming an alternative financial institution compliant with sharia, emphasising the principles of mutual aid, transparency, and adherence to Islamic ethical values. This study underscores the need to implement a mudharabah model that integrates the aspect of worship values so that sharia insurance not only functions as a financial instrument but also as a medium for spiritual and social strengthening within the community. The results of the analysis can serve as a basis for developing more sustainable sharia insurance products that carry the value of worship.